57Fe-Enrichment effect on the composition and performance of Fe-based O2-reduction electrocatalysts. Issue 15 (9th April 2021) - Ebner, Kathrin; Ni, Lingmei; Saveleva, Viktoriia A.; Le Monnier, Benjamin P.; Clark, Adam H.; Krumeich, Frank; Nachtegaal, Maarten; Luterbacher, Jeremy S.; Kramm, Ulrike I.; Schmidt, Thomas J.; Herranz, Juan
Abstract : In this work, we study how the performance and composition of platinum-group metal free catalysts of the Fe–N–C type are affected upon employing  57 Fe-enriched precursors in their synthesis. Abstract : Pt-group metal (PGM)-free catalysts of the Me–N–C type based on abundant and inexpensive elements have gained importance in the field of oxygen reduction reaction (ORR) electrocatalysis due to their promising ORR-activities. Their insufficient stability, however, has fueled the interest in obtaining an in-depth understanding of their composition, which requires highly sensitive techniques compatible with their low metal contents (typically <5 wt%). In the particular context of iron-based materials, 57 Fe-Mössbauer spectroscopy is often used to provide such compositional information, but requires (partially) 57 Fe-enriched precursors. As a consequence, the extrapolation of conclusions drawn from Mössbauer measurements on 57 Fe-enriched catalysts to equivalent materials with the standard isotope distribution relies on the assumption that the metal precursor's isotopic profile does not affect the catalysts' composition and ORR-activity. To verify this hypothesis, in this study we prepared two series of Fe-based catalysts using distinctively different synthesis approaches and various relative contents of 57 Fe-enriched precursors, and observed that the extent of the latter parameter significantly affected the catalysts' ORR-activity. This effect was successfully correlated with the Fe-speciation of the catalysts inferred from the characterization of these samples with Mössbauer and X-ray absorption spectroscopies. Ultimately, these results highlight the crucial importance of verifying the consistency of the catalysts' activity and composition upon comparing standard and 57 Fe-enriched samples.